The textuality of soulwork : Jack Kerouac's quest for spontaneous prose - Hunt, Tim, 1949- (Editorial theory and literary criticism., 2014)
Tim Hunt's The Textuality of Soulwork: Jack Kerouac's Quest for Spontaneous Prose examines Kerouac's work from a new critical perspective with a focus on the author's unique methods of creating and working with text. Additionally, The Textuality of Soulwork delineates Kerouac's development of "Spontaneous Prose" to differentiate the preliminary experiment of On the Road from the more radical experiment of Visions of Cody, and to demonstrate Kerouac's transition from working within the textual paradigm of modern print to the textual paradigm of secondary orality. From these perspectives, Tim Hunt crafts a new critical approach to Beat poetics and textual theory, marking an important contribution to the current revival of Kerouac and Beat studies underway at universities in the U.S. and abroad, as reflected by a growing number of conferences, courses, and a renewal in scholarship. -- Publisher